2018
DOI: 10.3390/w10121847
|View full text |Cite
|
Sign up to set email alerts
|

Hydro-Geochemical Assessment of Groundwater Quality in Aseer Region, Saudi Arabia

Abstract: Saudi Arabia is an arid country with very limited water resources. The absence of surface water bodies along with erratic rainfall renders groundwater as the most reliable source of potable water in arid and semi-arid regions globally. Groundwater quality is determined by aquifer characteristics regional geology and it is extensively influenced by both natural and anthropogenic activities. In the recent past, several methodologies have been adopted to analyze the quality of groundwater and associated hydro-geo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 77 publications
(34 citation statements)
references
References 31 publications
1
33
0
Order By: Relevance
“…The groundwater samples which were tested indicate Mg 2+ /Ca 2+ ratios above 1 (Table 4) however, they fall below the seawater range implying that other sources are responsible for salinization of groundwater such as (reverse cation exchange, dolomite dissolution processes or sewage invasion). To define freshwater and seawater mixing SO 4 2− /Cl − ratio is used as a natural tracer, in seawater the value of (SO 4 2− /Cl − ) * 1000 is found to be 103.4 and, as established from these values the quality of groundwater can be classified into two clusters (i) samples with a SO 4 2− /Cl − ratio similar to seawater, and (ii) samples with a ratio of SO 4 2− /Cl − ratio more than 300, mainly influenced by dissolution of evaporates according to Mallick et al (2018). In the present study, the ratio of (SO 4 2− /Cl − ) * 1000 ranges from 0 to 100; none of the samples are above 300 indicating no influence of seawater on groundwater.…”
Section: Indication Of Salinizationmentioning
confidence: 78%
“…The groundwater samples which were tested indicate Mg 2+ /Ca 2+ ratios above 1 (Table 4) however, they fall below the seawater range implying that other sources are responsible for salinization of groundwater such as (reverse cation exchange, dolomite dissolution processes or sewage invasion). To define freshwater and seawater mixing SO 4 2− /Cl − ratio is used as a natural tracer, in seawater the value of (SO 4 2− /Cl − ) * 1000 is found to be 103.4 and, as established from these values the quality of groundwater can be classified into two clusters (i) samples with a SO 4 2− /Cl − ratio similar to seawater, and (ii) samples with a ratio of SO 4 2− /Cl − ratio more than 300, mainly influenced by dissolution of evaporates according to Mallick et al (2018). In the present study, the ratio of (SO 4 2− /Cl − ) * 1000 ranges from 0 to 100; none of the samples are above 300 indicating no influence of seawater on groundwater.…”
Section: Indication Of Salinizationmentioning
confidence: 78%
“…Municipal or domestic sewage waste, fertilizers, and atmospheric precipitation are the primary sources of Clions in groundwater (Mallick et al 2018). Low percentages (up to 3 %) of the samples were found to have Clvalues exceeding the WHO recommended limits for drinking water, as given in Table 3.…”
Section: Anionsmentioning
confidence: 99%
“…Hiscock et al (1995) assessed the groundwater vulnerability and showed that the GIS is appropriate for the information extraction and is flexible in revising the classification plan. Mallick et al (2018) assessed the quality of groundwater in the Aseer region of Saudi Arabia. Their research showed that geochemical modeling has an important role in identifying the effective factors of groundwater quality.…”
Section: Introductionmentioning
confidence: 99%